Xenoliths from Cretaceous lamprophyres of Alcsútdoboz-2 borehole, Transdanubian Central Mountains, Hungary - Szabó Csaba (Acta mineralogica-petrographica, 1985)
Lower Triassic sediments of Alcsútdoboz-2 borehole (30 km W of Budapest (are cross-cut by alkaline lamprophyre dykes. These dykes contain xenoliths (megacrysts, ultramafic rocks, alkaline magmatité, quartzite inclusions and carbonatic evaporites) originated from different depths. Ultramafics contain phlogopite which is characteristic for lherzolite nodules of mantle origin. The alkaline magmatité xenoliths indicate contact of the melt with an alkaline intrusion in depth, which may bear significant economic importance.